The invisible hand in entrepreneurial process: bricolage in emerging economies. (1st January 2013) - Winkel, Doan; Vanevenhoven, Jeff; Yu, Andy; Bronson, James
The entrepreneurial process in emerging economies is receiving more interests but the critical role of bricolage is still in dearth. Entrepreneurs in these highly uncertain and dynamic environments discover, develop, and exploit opportunities with limited and idiosyncratic resources. They also navigate the entrepreneurial process within restrictive and unsupportive institutional environments. In this dynamic and often restrictive setting, entrepreneurs wanting to capitalise on opportunities must be able to manage with novel combinations of existing resources. Bricolage is therefore a relevant process in this entrepreneurial environment. This article argues that bricolage is a key mechanism to explore and explain entrepreneurship in emerging economies.